2021
DOI: 10.1253/circrep.cr-21-0103
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Personalized Assessment of Disease-Related Knowledge Among Patients With Congenital Heart Disease ― Development and Validation of the Japanese Version of the Leuven Knowledge Questionnaire for Congenital Heart Disease ―

Abstract: Background: Disease understanding in patients with congenital heart disease is important in transitional and lifelong care. This study aimed to develop the Japanese version of the Leuven Knowledge Questionnaire for Congenital Heart Disease (LKQCHD) and identify factors associated with disease-related knowledge. Methods and Results:After confirming the content and face validity of the scale, a questionnaire including the LKQCHD was distributed to 59 eligible patients aged >16 years attending a university hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, children with CHD often do not have a good understanding of the disease. Patients demonstrated a poor level of knowledge on all five thematic subscales (knowledge about CHD diagnosis, cardiovascular risk factors, symptoms of deterioration, endocarditis, and reproductive issues) [ 4 ], and other studies have consistently reported additional inadequacies [ 5 - 7 ]. Furthermore, young patients relied more on the information provided by their parents than on the information provided by their doctors [ 8 ], and the people who explained the disease for the first and subsequent times were reported to be "parents," "doctors," and "parents and doctors" in that order [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, children with CHD often do not have a good understanding of the disease. Patients demonstrated a poor level of knowledge on all five thematic subscales (knowledge about CHD diagnosis, cardiovascular risk factors, symptoms of deterioration, endocarditis, and reproductive issues) [ 4 ], and other studies have consistently reported additional inadequacies [ 5 - 7 ]. Furthermore, young patients relied more on the information provided by their parents than on the information provided by their doctors [ 8 ], and the people who explained the disease for the first and subsequent times were reported to be "parents," "doctors," and "parents and doctors" in that order [ 9 ].…”
Section: Introductionmentioning
confidence: 99%